Dynamic modulated brachytherapy (DMBT) for rectal cancer. Issue 1 (26th December 2012) - Webster, Matthew J.; Devic, Slobodan; Vuong, Te; Yup Han, Dae; Park, Justin C.; Scanderbeg, Dan; Lawson, Joshua; Song, Bongyong; Tyler Watkins, W.; Pawlicki, Todd; Song, William Y.
Abstract : Purpose: : All forms of past and current high‐dose‐rate brachytherapy utilize immobile applicators during treatment delivery. The only moving part is the source itself. This paradigm misses an important degree of freedom that, if explored, can in some instances produce previously unachievable dose conformality; that is, the dynamic motion of the applicator itself during treatment delivery. Monte Carlo and treatment planning simulations were used to illustrate the potential benefits of moving applicators for rectal cancer applications in particular. This concept is termed dynamic modulated brachytherapy (DMBT). Methods: : The DMBT system uses a high‐density, 18.0 g/cm 3, 45 mm long tungsten alloy shield, cylindrical in shape, with a small window on one side to encapsulate a 192 Ir source, to create collimation that results in a highly directional beam profile. This shield can be dynamically translated and rotated, using an attached robotic arm, during treatment to create a volumetric modulated arc therapy‐type delivery, but from inside the rectal cavity. Monte Carlo simulations and planning optimization algorithms were developed inhouse to evaluate the effectiveness of this new approach using 36 clinical treatment plans comprised of 13 patients each treated using the intracavitary mold applicator (ICMA, Nucletron, The Netherlands) to quantify the potential clinical benefit. The prescription dose was 10 Gy/fx and the group had an average clinical target volume of 9.0 ± 3.5 cm 3 . Ideal phantom geometries were used to evaluate the impact of various shield dimensions and designs on the resulting plan quality. Results: : Simulations of ideal phantom geometries found that shields as small as 10 mm in diameter can produce high quality plans. For the clinical patient cases, compared to the ICMA, for equal prescription tumor coverage, the DMBT plans provided >30% decrease in D5 (high dose volume) resulting in a ∼40% decrease in dose heterogeneity index. In addition, mean dose and D98 showed a reduction (typically 40%–60%) on all critical structures evaluated. However, for a 10 Gy prescribed dose there was an increase in total treatment time on average from 7.6 to 20.8 min for a source with an air‐kerma strength of 40.25 kU (10 Ci). Conclusions: : Dosimetric properties of a novel DMBT system have been described and evaluated. Comparison with the ICMA commercial applicator has shown it to be a prospective step forward in high‐dose‐rate brachytherapy 192 Ir technology. Dynamic motion of an applicator during treatment, for any applicator and site in general, can provide additional degrees of freedom that, if properly considered, can potentially increase the plan quality significantly.